„Einmal furchtlos vor Menschen sein und kühn!“ Max Zweigs Arbeit am Gründungsmythos Israels - Eke, Norbert Otto (Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

Schmerz und Ironie. Mascha Kaléko und die deutsche Kultur (mit Blick auf Heinrich Heine) - van Laak, Lothar (Zwischen den Sprachen - mit der Sprache?)

Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel

"Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices" - Strauß, Sara (Victorian Ideologies in Contemporary British Cultures)

"Silvia Pellicer-Ortín, Julia Tofantšuk (eds.), Women on the Move. Body, Memory and Femininity in Present-Day Transnational Diasporic Writing" - Strauß, Sara (Miranda: Multidisciplinary Peer-Reviewed Journal on the English-Speaking World)

Portfolioarbeit im Kontext von Sprachenunterricht. Neue internationale Entwicklungen

Schreibprozesse unterstützen: Der Einsatz von Portfolios und Schreibberatung im DaF- und DaZ-Unterricht - Ballweg, Sandra (Produktion und Partizipation in Deutsch als Fremd- und Zweitsprache: Sprechen - Schreiben - Mitreden. Dokumentation der siebten Gesamtschweizerischen Tagung für Deutschlehrerinnen und Deutschlehrer)

Portfolio im Kontext von Mehrsprachigkeit - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Erst-, Zweit- und Mehrsprachenerwerb - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Die Ethik der Widersetzlichkeit. Theoretische und literarische Transformationen der Antigone, Berlin u.a.: Peter Lang (Historisch-kritische Arbeiten zur deutschen Literatur) - Böker, Ines

Schnelles inhaltliches Feedback zu Entwürfen - Scharlau, Ingrid; Heuer, Claudia (Wissenschaftliches Lesen und Schreiben vermitteln)

Psychological Feasibility of a Virtual Cycling Environment for Human-in-the-Loop Experiments - Stratmann, Lukas; Buse, Dominik S.; Heinovski, Julian; Klingler, Florian; Sommer, Christoph; Tünnermann, Jan; Scharlau, Ingrid; Dressler, Falko (INFORMATIK 2019: 50 Jahre Gesellschaft für Informatik – Informatik für Gesellschaft (Workshop-Beiträge))

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

Handbuch Text und Gespräch - Markewitz, Friedrich (Gesprächsforschung – Online Zeitschrift zur verbalen Interaktion)

Fachsprachen. Die Konstruktion von Welten - Markewitz, Friedrich (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Grundlagen und Paradigmen einer systemtheoretisch fundierten Textsortenlinguistik – Eine kritische Bestandsaufnahme - Markewitz, Friedrich (Zeitschrift für Literaturwissenschaft und Literatur (LiLi))

Intergenerationelle Beziehungen in der Familie - Buhl, Heike M.; Sommer, Sabrina (Psychotherapie im Alter)
Beziehungen zwischen Erwachsenen und ihren Eltern sind durch Interdependenzen und Dependenzen gekennzeichnet. Während das Zusammenleben von Familien mit Kindern im mittleren Erwachsenenalter dabei ganz überwiegend durch Interdependenz geprägt ist, nehmen im Alter Dependenzen durch gesundheitliche Beeinträchtigungen der Eltern zu. Mit Blick darauf werden im Artikel behaviorale, kognitive und emotionale Merkmale von Eltern-Kind-Beziehungen erläutert und theoretisch in zentrale Konzepte eingebettet. Das Verhalten ist durch Solidarität zwischen den Generationen, aber auch durch Aspekte des Einflusses innerhalb der Beziehung und aufeinander, gekennzeichnet. Um Familienkognitionen zu beschreiben, werden die verwandten Konzepte der Individuation und der filialen Reife herangezogen. Verhalten, wie auch Kognitionen, sind eng mit dem dritten Beziehungsmerkmal, der Affektivität verknüpft, das neben positiven auch negative Gefühle sowie Ambivalenzen umfasst.

Feedback in internet-based self-assessments and its effects on acceptance and motivation - Bohndick, Carla; Menne, Christina; Kohlmeyer, Susanne; Buhl, Heike M. (Journal of Further and Higher Education)
Internet-based self-assessments (ISAs) are tools used to support finding the right educational fit for higher education (HE) students. ISAs typically consist of a questionnaire followed by a feedback report about the results. It is unknown how the characteristics of the feedback report itself affect individuals’ acceptance and motivation to follow the advice from the report. Literature on feedback in general has suggested relationships between acceptance of feedback and motivation, feedback sign (positive versus negative) and regulatory focus (promotion focus versus prevention focus), influence acceptance and the motivation to develop. To investigate if these findings are transferable to the context of ISAs, we conducted an online study with N = 249 German university students (73% female; M = 22.84 years of age (SD = 3.73)) and a bogus self-assessment. Feedback sign was manipulated randomly, and the regulatory focus was measured by values. Regression analyses indicate a positive effect of positive feedback sign, but no differences regarding regulatory focus.

Bedingungen elterlichen Unterstützungsverhaltens beim Lesen im Grundschulalter. Eine Untersuchung relevanter Prozessmerkmale - Hilkenmeier, Johanna; Wiescholek, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)